Description of a new flat gecko (Squamata: Gekkonidae: Afroedura) from Mount Gorongosa, Mozambique - Branch, William R.; Guyton, Jennifer A.; Schmitz, Andreas; Barej, Michael F.; Naskrecki, Piotr; Farooq, Harith; Verburgt, Luke; Rödel, Mark-Oliver (Zootaxa, 2017)
A new species of flat gecko, Afroedura gorongosa sp. nov., is described from Gorongosa National Park, Sofala Province, central Mozambique. The new species is morphologically similar to A. transvaalica and A. loveridgei, from both of which it is genetically distinct (15–17% divergence; 400 bp of 16S rRNA). Morphologically it can be distinguished from both species by having fewer midbody scale rows (97–101) and a higher number of precloacal pores in males (8–13). The type series was collected on the western flanks of Mount Gorongosa (900 and 1100 m a.s.l.) in comparatively cool and moist microclimates, where it is threatened by illegal deforestation. Additional material was collected as low as 212 m a.s.l. on an inselberg near Mount Gorongosa. The new discovery adds to the growing number of endemic montane reptiles discovered in Mozambique in recent years, and highlights the need for a national conservation assessment of the country’s herpetofauna and continued protection of the Mount Gorongosa region.